Uniform Liquid Crystal Alignment Properties on Ion-Beam Irradiated Indium Zinc Oxide Films with Stable Electro-Optical Performances - Oh, Byeong-Yun (THE TRANSACTION OF THE KOREAN INSTITUTE OF ELECTRICAL ENGINEERS P, 2019)
The uniform liquid crystal (LC) molecules alignment was successfully achieved by using ion-beam irradiated indium zinc oxide (IZO) films. Conducting the solution process as a film deposition method, the IZO film was deposited on the glass substrate and ion-beam with various energy was irradiated on the IZO film. To verify the LC alignment properties, anti-parallel cell was fabricated and polarizing optical microscope was used. Field emission scanning electron microscope was adopted to observe the surface morphology of the IZO Film. Furthermore, X-ray photoelectron spectroscopy was used to investigate the chemical composition change as ion-beam energy increased. The strong ion-beam irradiation induced the breakage of metal oxide bonds on the surface and this increased the surface anisotropic characteristics which greatly affected on the LC alignment. Finally, electro-optical performance of the twisted-nematic cell was measured. KCI Citation Count: 0